2023
DOI: 10.3389/fped.2023.1114207
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of canakinumab as a second line biologic after tocilizumab treatment failure in children with systemic juvenile idiopathic arthritis: A single-centre cohort study using routinely collected health data

Abstract: BackgroundA significant number of systemic juvenile idiopathic arthritis (sJIA) patients discontinue biologic disease-modifying antirheumatic drugs (bDMARDs) due to lack of efficacy or safety concerns. Studies of biologic therapy switch regimens in sJIA are required.MethodsPatients with sJIA who switched from tocilizumab (due to lack of efficacy or safety) to canakinumab (4 mg/kg every 4 weeks) and were hospitalized at the rheumatology department from August 2012 to July 2020 were included. Primary efficacy ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Of note, many patients required the introduction of cDMARDs in both groups; in this regard, concomitant use of conventional immunosuppressants could have a role in the final treatment outcome, and this has been the focus of other studies ( 20 ). The present study confirms the results recently proposed by Alexeeva et al ( 21 ) regarding the effective role of CAN in 46 patients with sJIA previously administered the IL-6 inhibitor tocilizumab, extending the concept to the whole spectrum of Still’s disease (both sJIA and AOSD) and confirming the results, regardless of the biologic agents previously used.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, many patients required the introduction of cDMARDs in both groups; in this regard, concomitant use of conventional immunosuppressants could have a role in the final treatment outcome, and this has been the focus of other studies ( 20 ). The present study confirms the results recently proposed by Alexeeva et al ( 21 ) regarding the effective role of CAN in 46 patients with sJIA previously administered the IL-6 inhibitor tocilizumab, extending the concept to the whole spectrum of Still’s disease (both sJIA and AOSD) and confirming the results, regardless of the biologic agents previously used.…”
Section: Discussionsupporting
confidence: 92%
“…We found five studies on anti-IL-1 agents and the risk of cancer: two analyzing various anti-IL-1 [ 89 , 90 ], two on canakinumab [ 91 , 92 ] and one on rilonacept [ 93 ]. All of the studies, including an SR with > 10,000 patients with cryopyrin-associated periodic syndromes (CAPS) treated with anti-IL-1 therapy, showed that these drugs did not increase the rate of neoplasms compared to the general population [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Horneff G et al found that tocilizumab was more frequently discontinued due to intolerance compared to IL-1 inhibitors ( 12 ). Alexeeva E et al had described that 82% of patients with sJIA achieved remission with one-year canakinumab therapy after tocilizumab treatment failure ( 13 ). Besides, He T et al had described tocilizumab-induced hypofibrinogenemia in patients with sJIA, which was not observed in patients with canakinumab therapy ( 14 ).…”
Section: Discussionmentioning
confidence: 99%